A validation model to reduce non-contributory time based on Lean tools: Case of a construction company in Perú - Cabrera, Olenka (2023)
The construction industry has long been suffering from high rates of non-contributory time. Construction processes are likely to include time, which is sometimes lost for non-value-adding operations resulting in time waste. Considering the large percentage of lost time in all operations, this study aims to reduce the high rate of non-contributory time (NCT) in construction services. To test the management model, a Peruvian company was selected as a study case. In this respect, a management model based on mostly implemented Lean tools such as Kanban, 5S, and TPM was utilized. It is of utmost importance to emphasize that this proposal aims to reduce the NCT by up to 25%, as well as reduce the number of orders generated with delay, and eventually reduce the loss or damage of materials and equipment stoppages.